Crime Prevention in Terms of Designing Public Space and the Role of Private Security - Stajić, Ljubomir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Concern about the security of public spaces has become increasingly important in the last thirty years, both in the public service (police) and in private security which is responsible for protection of individual private facilities. It has been concluded that the study of public space design in terms of security is as important as the study of social and other factors of criminal behavior. Modern architectural solutions must take into account a design of space and facilities that prevents and obstructs the exercise of criminal actions to a maximum. Security design should make crime dangerous, less desirable and less justified, i.e. it should change the perception that potential criminals have of the risks of criminal behavior in terms of greater opportunities for its detection and arrest. The paper presents the criteria which should be followed when designing a public space, its effect on the behavior of criminals and notes on how badly designed public space reduces the effects of formal oversight by private security guards and the police. Most of the work is related to the case study of Block 21 in New Belgrade as a typical representative of the public space that has undergone numerous transformations over the past 50 years. There are very important indicators of how design changes of the area affected the state of crime.